Hubungan Tingkat Pendidikan, Status Pekerjaan, dan Lama Bertugas Jumantik terhadap Pemeriksaan Jentik Rutin (PJR) di Kelurahan Pudakpayung Kota Semarang - Sari, Arlyn Manggar; Hestiningsih, Retno; Martini, Martini; Kusariana, Nissa (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Personal Background: The Dengue Hemorrhagic Fever (DHF) cases in Semarang City ranked seventh highest in Central Java in 2022 with an Incidence Rate (IR) of 42.41 per 100,000 population. The district with the highest number of DHF cases was Banyumanik District, reaching 712 cases of dengue fever. Pudakpayung Sub-district experienced a more than threefold increase in DHF cases in 2022. One mandatory DHF prevention program is Routine Larval Survey (PJR) conducted by mosquito control workers (Jumantik). Due to the lack of consistent and optimal PJR implementation in Pudakpayung Sub-district, this research was conducted to investigate the relationship between educational level, employment status, and length of service of Jumantik with the implementation of PJR in Pudakpayung Sub-district. Method: The method used is analytical with a cross-sectional study design. The sample size is 115, determined by simple random sampling with the condition of one Jumantik sample per neighborhood unit (RT) in all neighborhood administrative areas (RW) of Pudakpayung Sub-district. Result The results of this study indicate that the majority of respondents have a high level of education, with 86 respondents (74.8%), are unemployed, totaling 84 respondents (73%), have been on duty for a long time, totaling 67 respondents (58.3%). Additionally, 84 respondents (73%) comply with implementing PJR according to regulations. Conclusion: Efforts are needed to cultivate understanding and disseminate information through various methods evenly to improve the knowledge level of Jumantik as the implementer of the dengue fever prevention program.